2006
DOI: 10.1002/jat.1127
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of aflatoxin B1-initiated hepatotoxicity in rat by marine algae extracts

Abstract: Chemoprevention by extracts of Laurencia obtusa (E1) and Caulerpa prolifera (E2) collected from the Egyptian coast of the Red Sea against aflatoxin B(1) (AFB(1))-initiated hepatotoxicity in female Sprague-Dawley rats has been studied. Animals were fed aflatoxin-contaminated diet (3 mg kg(-1) diet) for 6 days then treated orally with pure aflatoxin B(1) (AFB(1)) (200 microg kg(-1) b.w.) for 4 days either in combination with or before E1 or E2 administration (50 mg kg(-1) b.w.). AFB(1) resulted in a signicant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 87 publications
5
47
0
2
Order By: Relevance
“…Normally, no production of this marker occurs in the adult cells, but it can be secreted when these cells transformed to cancer cells. Similar finding was observed by Sell et al [23] and Abdel-Wahhab et al [24] who found that aflatoxins feeding to ducks for longer term and rats for 6 days produced an elevation in the level of serum AFP. Our result may be attributed to estrogen like effect of ZEN, because estrogens can interact with specific receptors called estrogen receptors (ER) in the liver and exerting a number of toxic effects, including liver adenomas and hepatocarcinomas [25,26].…”
Section: Discussionsupporting
confidence: 87%
“…Normally, no production of this marker occurs in the adult cells, but it can be secreted when these cells transformed to cancer cells. Similar finding was observed by Sell et al [23] and Abdel-Wahhab et al [24] who found that aflatoxins feeding to ducks for longer term and rats for 6 days produced an elevation in the level of serum AFP. Our result may be attributed to estrogen like effect of ZEN, because estrogens can interact with specific receptors called estrogen receptors (ER) in the liver and exerting a number of toxic effects, including liver adenomas and hepatocarcinomas [25,26].…”
Section: Discussionsupporting
confidence: 87%
“…This effect could be induced by the dose of aflatoxin received, since it has been reported that AFB 1 induces reduction of food intake in some animal species, including rats and birds, in a dose-dependent manner [33]. In addition, toxicological studies in rats have shown that AFB 1 consumption may produce a significant decrease of serum leptin levels [34]. Leptin concentration is usually associated with the high levels of cortisol and interleukin-6, which act together to influence the feeding response [35].…”
Section: Discussionmentioning
confidence: 96%
“…It is well documented that CCl 4 enhanced lipid peroxidation (Abdel-Wahhab et al, 2006;El Denshary et al, 2012). The CCl 4 induces the peroxidation of lipids that damage the membranes of liver cells and organelles.…”
Section: Mild Chronic Hepatitismentioning
confidence: 99%